PENGARUH MODEL DISCOVERY LEARNING DAN MEDIA REALIA TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SD - Susiana Sofiahani Evidawati; Erny Roesminingsih; Titi Chandrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Developing students' critical thinking skills is crucial in equipping them to solve problems independently. Learning models and media, particularly discovery learning and realia media, are essential for enhancing critical thinking skills. This is because students are motivated to learn independently and take an active role in discovering principles and ideas through problem-solving in discovery learning. Furthermore, using realia media allows students to gain firsthand knowledge of the subject. Fifth-grade students at SD Negeri Gugus 1 in Slahung District, Ponorogo, were the subjects of this study, which aimed to determine how integrating the discovery learning paradigm with realia media affected their critical thinking capacity. A quantitative approach with a correlational design was used in this investigation. A sample of 33 fifth-grade students from SD Negeri 1 Caluk (15 students) and SD Negeri 2 Caluk (18 students) were recruited. Questionnaires and tests were used as data collection instruments. A series of tests, including validity, reliability, normality, homogeneity, and hypothesis testing with correlation tests, were conducted. The results show that the discovery learning model significantly and strongly influences students' critical thinking skills, realia media significantly and strongly influences students' critical thinking skills, and simultaneously, the discovery learning model and realia media significantly influence students' critical thinking skills.